Emotional Intelligence and Its Important Role - Utaminingsih, Esty Setyo; Puspita, Maria Ayu (Jurnal Ilmiah Profesi Pendidikan, 2023)
Systems prioritizing intelligence or academic values harm students. Lack of emotional control makes children tend to behave rudely and lack empathy. Worse, to the point of bullying behavior. This study aims to examine more about the emotional intelligence of elementary school students. The method in this study uses the method of literature review. The results of this study show that high-grade elementary school students begin to realize that the harsh expression of emotions is not welcome; they begin to learn to control the expression of their emotions. Positive emotions can lead students to optimism and good self-efficacy. Positive emotions stimulate happiness hormones so that feelings become calmer and the brain can think better, so students are fully attentive to a series of learning processes. Lack of emotional control makes students not enthusiastic to follow the learning process. It can be concluded that emotional intelligence needs to be instilled since elementary school to support academic achievement and success.